Global organization of phenylpropanoid and anthocyanin pathways revealed by proximity labeling of trans-cinnamic acid 4-hydroxylase in Petunia inflata petal protoplasts - Aravena-Calvo, Javiera; Busck-Mellor, Silas; Laursen, Tomas (Frontiers in Plant Science, 2024)
The phenylpropanoid pathway is one of the main carbon sinks in plants, channeling phenylalanine towards thousands of products including monolignols, stilbenes, flavonoids and volatile compounds. The enzymatic steps involved in many of these pathways are well characterized, however the physical organization of these enzymes within the plant cell remains poorly understood. Proximity-dependent labeling allows untargeted determination of both direct and indirect protein interactions in vivo, and therefore stands as an attractive alternative to targeted binary assays for determining global proteinprotein interaction networks. We used TurboID-based proximity labeling to study protein interaction networks of the core phenylpropanoid and anthocyanin pathways in petunia. To do so, we coupled the endoplasmic reticulum (ER) membrane anchored cytochrome P450 cinnamic acid 4-hydroxylase (C4H, CYP73A412) from Petunia inflata to TurboID and expressed it in protoplasts derived from anthocyanin-rich petunia petals. We identified multiple soluble enzymes from the late anthocyanin pathway among enriched proteins, along with other C4H isoforms, and other ER membrane anchored CYPs. Several of these interactions were subsequently confirmed by bimolecular fluorescence complementation (BiFC). Our results suggest that C4H co-localizes with enzymes from the phenylpropanoid-and downstream anthocyanin pathways, supporting the idea that C4H may serve as ER anchoring points for downstream metabolic pathways. Moreover, this study demonstrates the feasibility of using protoplasts to perform global mapping of protein network for enzymes in their native cellular environment.